The Impact of tiktok Shops on SMEs Actors - Adytiya, Yusuf; Zainuddin, Kusmawardany; Muiz, Abdul (Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2023)
In the increasingly advanced digital era, the retail industry has witnessed some important paradigms in offline and online stores. In addition to technology development, both platforms offer different opportunities. Online stores are a popular trend among consumers who want to shop easily and conveniently through online platforms. But over time, market participants realized that the presence of online shopping posed risks to them. For example, there is fierce competition between offline and online stores. In this context, tiktok stores have become a new threat to traditional retailers, and market traders need to be able to compete with the prices offered by tiktok stores, which are generally cheaper because they have no physical operating costs. This study focuses on the impact of tiktok stores on Small and Medium Enterprises (SMEs). The method used in this study is qualitative, collecting non-numerical data such as observational interviews and content analysis. This study targets market traders and actors behind online stores, specifically in Surabaya, to support data obtained. Through this study, researchers made decisions about aspects of this study. Research conclusions: (1) The existence of online stores has made many bankrupt market traders become online store players, because online stores have more profit prospects than market traders. (2) The busyness of online stores eliminates the possibility of extinction of market traders, because online shopping involves high risks of fraud, such as counterfeiting, etc., which may cause financial losses to consumers. Market Traders are more secure than online stores due to their relative reliance on direct interaction.